Remoção de sulfeto de hidrogênio de biogás a partir de soluções de ferro III produzidas por eletrólise: avaliação da cinética química de purificação e regeneração - Cavaler, Jadiane Paola (2021)
Biogas is a gas mixture from the anaerobic digestion of organic waste, composed of methane (CH4), carbon dioxide (CO2) and other trace gases, such as hydrogen sulfide (H2S). It has great potential for energy generation, as it has high calorific value. However, for its use, it is necessary that it be subjected to H2S removal processes, as this in high concentrations causes potential damage to human health, in addition to being highly corrosive. In the search for methodologies for the purification of biogas, chemical absorption systems have shown to be very efficient in removing hydrogen sulfides. The present work sought to produce three iron solutions for biogas purification, with a concentration of 0.35 gL-1 defined in preliminary tests, using an electrolysis system with electrodes of iron and NaCl as electrolyte, changing only the electric current and fixing the time in 8.5 minutes. The concentrations of Fe2 +, Fe3 + and FeTotal of the solutions were evaluated immediately after their preparation and during the purification tests, minute by minute for 14 min. The iron solution was introduced into a column, then used to remove the H2S from the biogas, and then the solution was regenerated with the passage of air for 20 minutes. From the kinetic results for the purification and regeneration, kinetics adjustments were sought for the two stages, using the first and second order models, in addition to the test with the sigmoidal model -Logistic. For data treatment, RMSE was used from Microsoft Excel and the solver platform. The kinetic model obtained for both stages was the sigmoidal, also known as logistic.